2021
DOI: 10.1002/ece3.7906
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal maintenance of flora in the Himalaya biodiversity hotspot: Current knowledge and future perspectives

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 182 publications
1
20
0
Order By: Relevance
“…In our study, most populations were concentrated in the vicinity of the Yulong Mountain (approximately at the intersection of latitude 27°N and longitude 100°E). The high species richness of the northern LRGR is consistent with the view that orogeny (which was more intense toward the northern LRGR) was responsible for species diversification in the Himalaya/Hengduan Mountains region ( Wambulwa et al, 2021 ). The observed congruence in species and genetic diversity patterns is a well-known phenomenon ( Vellend and Geber, 2005 ; Vellend et al, 2014 ) and has been observed in both plant and animal communities ( Fan et al, 2018 ; Hu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, most populations were concentrated in the vicinity of the Yulong Mountain (approximately at the intersection of latitude 27°N and longitude 100°E). The high species richness of the northern LRGR is consistent with the view that orogeny (which was more intense toward the northern LRGR) was responsible for species diversification in the Himalaya/Hengduan Mountains region ( Wambulwa et al, 2021 ). The observed congruence in species and genetic diversity patterns is a well-known phenomenon ( Vellend and Geber, 2005 ; Vellend et al, 2014 ) and has been observed in both plant and animal communities ( Fan et al, 2018 ; Hu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…As in most regions in the Hengduan Mountains, most of the cities, villages, and farms in Mount Tai were distributed at low elevations and have been for thousands of years. This long history of disturbance may have exacerbated the evolution and adaptation of biodiversity (Pan et al, 2019; Wambulwa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Dated phylogenies of Theaceae indicate that Tribe Theeae, Genus Camellia and Species [Camellia sinensis (L.) O. Kuntze] diverged from their ancestors ∼50 Mya (million years ago), ∼15 Mya, and ∼625 Kya, respectively (38). The two time periods generally coincide with onset of the Tibetan Plateau uplift, rise of the Himalaya/extrusion of Indochina block, and the Mid-Pleistocene glaciations [ (43)(44)(45); Figure 2], events that are thought to have influenced the distribution of plant species and driven lineage divergence in the region (46)(47)(48)(49). Furthermore, genomic analyses and Bayesian computation models indicate that CSS and CSA diverged from their last common ancestor in the middle to upper Pleistocene (25,50).…”
Section: Domestication History Of Teamentioning
confidence: 99%